Effects of food labels on consumers purchasing behavior in Malaysia - Abdul Latiff, Zul Ariff (2013)
Changes in the food environment, including the convenience foods, frozen foods and fast foods high in energy and fat content, has affected the views of the health conscious consumers in Malaysia. One approach to measure the health and safety consciousness among Malaysians is to measure the effect of food labeling on the public decision when purchasing food products. Food labeling offers a great deal of information on most packaged foods. This thesis examines both theoretical and practical use of food labeling for consumer products in Malaysia and tries to validate an extended theory of planned behavior (TPB) model on the data derived from the consumers in Malaysia. Today consumers are exposed to many labels in the food market. Therefore for Malaysian consumers, the existence of labels on food products has become a subject of interest. Some labels are misleading and can create confusion for consumers. Despite increasing the awareness among consumers, still many of them have problems with the understanding of scientific terms and concepts of food labels. The design of some labels is not consumer friendly or well-known by consumers. Therefore there is a need to explore if food labeling is an effective way of giving information regarding the food making process to consumers or how influential food labels are on the consumer purchasing choice. How consumer attitude, subjective and perceived behavior control will influence their intention to purchase food products based on labels. If the main concern of labeling is to convey the producer’s message to consumers; which of group consumers are willing to spend more time and pay higher prices for food products to receive the producers’ massage. The main objective of the study is to investigate the effect of food labels on Malaysian consumer purchasing behavior base on their intention. The specific objectives are to identify the level of importance of food labels on food products. Secondly to determine factors influencing consumer purchasing intention based on food labels. To examine the relationship between the influencing factors (such as attitude, subjective norm and perceived behavior control) on consumer purchasing intention based on food labels. The data is collected by stratified random sampling method from a self reported questionnaire administered to two thousand and fourteen (2014) consumers representing the entire races in Malaysia from May to September 2011. The consumer was interviewed in order to obtain their confidence on food label products. The questions asked include subjects based on awareness and knowledge, attitude toward food label, subjective norm, perceived behavior control, and intention toward food label. A Likert scale of one to 7 (1 representing strongly disagree and seven representing strongly agree) is used to measure consumer confidence on the statements formulated in relation to food label. In this study, the descriptive analysis, factor analysis, and structural equation model is applied to analyze the information. The findings indicate that the majority of the Malaysian consumers are aware of food labels on food products. Even though the results show that consumers do not always refer to a label on food product, but there is still enough proof to support that they are more careful in evaluating the food label of all types of food product by relating to the list of ingredients, nutrition, safety, price, halal and the food brand. Nevertheless, most consumers are able to differentiate the label on food products. Based on the factor analysis, the following four factors influence the purchase of food products with a label: attitude, subjective norm, perceived behavior control and intention toward food label. In general, various socio-economic factors significantly influence the probability of consumer confidence on the food labels. Misuses, modification to food label on food products have an adverse effect on a privately assured intention and overall business trading. The Malaysian government, policy makers, food manufacturers and related establishments ought to fulfill the needs of consumers to restore any lost confidence. There ought to be an economic coordination from the government to producers to promote and offer trustworthy and reliable food labeled food products.